Leadership Framework in Military Organization Change Management to Deal with Electronic Warfare Threats - Emanuel Ario Bimo; Amarulla Octavian; Suyono Thamrin; Rudy Laksmono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The vulnerability of electromagnetic spectrum use for military activities against electronic warfare threats requires military organizations to undertake changes. Leadership is a determining factor in the success of military organization change management to deal with electronic warfare threats. This study aims to develop a leadership framework in military organization change management for improving its capability in dealing with such threat. By employing descriptive qualitative approach and Context, Input, Process, and Product (CIPP) analysis, the result of this study indicates that the need for leadership in military organization change management stems from the external context of electronic warfare threats development and military organization’s internal context. The required leadership input to successfully implement changes consists of informal and formal influences that are distributed among the senior, middle, and junior levels personnel in military organization; which are required to conduct leadership process, namely directing, structuring, facilitating, social integration, and monitoring and controlling activities. The leadership products are change vision, strategy, and plans, conducive organization culture and work environment, competent personnel, and adequate hardware and software for implementing changes within the military organization to deal with electronic warfare threats.